Can Hyaluronic Acid Reduce Friction in the First Extensor Compartment? A Cadaveric Study - Rotem, Gilad; Badowski, Emma; Cohen, Matan J; Langohr, G. Daniel G; Kadar, Assaf (Journal of Wrist Surgery, 2025)
De Quervain's tenosynovitis (DQT), marked by pain and dysfunction from thickening of the first dorsal compartment, traditionally relies on treatments like corticosteroid injections, physiotherapy, braces, and surgery. This study explores hyaluronic acid (HA), recognized for its lubricating properties, as a nonsurgical alternative to improve tendon gliding at the tendon–retinaculum interface.Biomechanical cadaveric study.Eighteen cadaveric specimens of the first extensor tendon compartment were soaked in saline. Half were treated with HA and half with celestone soluspan. Friction between the abductor pollicis longus (APL) and extensor pollicis brevis (EPB) tendons against the extensor retinaculum was measured at wrist–thumb angles of 30 to 20 degrees and 30 to 0 degrees.HA significantly reduced friction by 18.7% compared with saline, with the greatest reduction observed in the EPB at the 30 to 20-degree angle.These findings indicate that HA may offer a promising nonsurgical treatment for DQT and support further clinical trials.Level of Evidence III.
Keywords: friction testing; gliding resistance; hyaluronic acid; De Quervain's tenosynovitis; corticosteroid; biomechanical; extensor tendons; hand surgery